TANGGUNG JAWAB SOSIAL PERUSAHAAN DAN DAMPAKNYA PADA KINERJA PEMASARAN - Dessy Novitasari; Waluyo Budi Atmoko; Ariefah Yulandari (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This study aims to determine corporate social responsibility and the effect of marketing performance on users of herbal and pharmaceutucal product at PT. Sido Muncul. emerging sido products. The level of marketing performance for users of PT. Sido Muncul products appears identified by the presence of corporate image, corporate social responsibility, and customer value for users of sido products. Marketing performance has an impact on corporate image, social responsibility, and customer value. Data collection was carried out through a questionnaire distributed to users of PT. Sido Muncul products. The sample in this study were 200 users of PT. Sido Muncul products. The sampling technique used was convenience sampling. This analysis uses SEM (Structural Equation Modeling) analysis and uses multiple regression analysis. The results in this study indicate that six hypothesis are supported. The variable of corporate social responbility affects on marketing performance. The variable of corporate social responbility affects on company image. The variable of customer value have a positive effect on company image. The variable of customer value have a positive effect on marketing performance. The variable of customer social responbility has a positive effect on customer value.